Nilai pendidikan sufistik lirik lagu “Tombo Ati” karya Sunan Bonang - Indriya (Ta'dibuna: Jurnal Pendidikan Islam, 2023)
Walisongo or Walisanga is known as the spreader of Islam in Java around the 1st century and was an intellectual figure who became a social reformer in his time. This research focuses on the lyrics of Tombo Ati by Sunan Bonang and examines the Sufism meaning of the lyrics, as well as their impact on strengthening Aqidah and forming Islamic character. In this research, the researcher used a library research method, where this research used various literature, including books, notes, and reports of previous research results, in collecting data. The results of the research obtained by the researchers are: first, Tombo Ati Lyrics is a social and cultural media that is a medium for education and strengthening Islamic values in Indonesian society; second, education which is characterized by the values of the teachings of ulama and displays self-identity to clarify the existence of Indonesian Muslims; third, the existence of Tombo Ati's lyrics. As an ancestral cultural heritage, its preservation should be preserved, as a result of the work of education and da'wah. Abstrak Walisongo atau Walisanga dikenal sebagai penyebar agama Islam di tanah Jawa sekitar abad ke-1, merupakan tokoh intelektual yang menjadi pembaharu masyarakat pada masanya. Penelitian ini fokus pada lirik Tombo Ati karya Sunan Bonang, dan mengkaji makna tasawuf liriknya, serta dampaknya terhadap penguatan Aqidah dan pembentukan karakter Islam. Dalam penelitian ini peneliti menggunakan metode penelitian kepustakaan, di mana penelitian ini menggunakan berbagai literatur baik buku, catatan, maupun laporan hasil penelitian terdahulu dalam mengumpulkan data. Hasil penelitian yang peneliti peroleh adalah pertama, Lirik Tombo Ati merupakan media sosial budaya yang menjadi media Edukasi dan Pemantapan Nilai-Nilai Islami pada masyarakat Indonesia; kedua, Pendidikan yang bercirikan nilai ajaran ulama serta menampilkan diri -identitas untuk memperjelas keberadaan umat Islam Indonesia; ketiga, keberadaan lirik Tombo Ati. sebagai warisan budaya leluhur, sudah sepatutnya dijaga kelestariannya, sebagai hasil karya Pendidikan dan Dakwah.